Change-of-direction, speed and jump performance in soccer players: a comparison across different age-categories - Loturco, I.; Jeffreys, I.; Abad, C. C. C.; Kobal, R.; Zanetti, V.; Pereira, L. A.; Nimphius, S. (Journal of Sports Sciences, 2020)
This study examined the age-specific development of vertical jump height, straight and change-of-direction (COD) speed, and COD deficit in one-hundred and eighty-two elite soccer players from different age-categories (U15, U17, U20, and Senior). All participants were players of two distinct clubs and were undertaking different training routines, as planned by their technical staff members. For this purpose, the soccer players performed: (1) squat and countermovement jumps; (2) a maximal 20-m linear sprint speed test, and (3) the Zigzag COD test. The magnitude-based inference approach and standardized differences were used to compare the age-groups. Sprint speed at longer distances (20-m) increased progressively across the age-ranges. In contrast, speed and acceleration performances at shorter distances (5-m) were better in U15 than in the other age-categories. The COD speed did not change throughout the younger categories but presented a meaningful decrease in the Senior category. Surprisingly, despite the progressive increase in volume and intensity of neuromuscular training from younger to older categories, the COD deficit presented a gradual increase across the age-groups. It is possible that simple modulation of the strength-power training program during the maturation process is not sufficient to produce faster adult players with enhanced ability to change direction. Therefore, coaches are strongly encouraged to implement specific COD training practices to tolerate braking at increasing running speeds and appropriate volume and intensity of soccer specific training throughout the players` specialization process.